The A SURVEY OF THE DECISION-MAKING STYLES OF WORKING PARAMEDICS AND STUDENT PARAMEDICS - Muteeb Showket Reshi , Asif Hussain, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Experiential (intuitive) and logical (conscious) thinking are two of the primary processes that underpin human decision-making. When it comes to making clinical choices, no one knows exactly how practising paramedics and student paramedics approach it. Methods: Ground ambulance paramedics and primary care paramedic students were asked to complete a survey. As part of the survey, demographic information and the Rational Experiential Inventory-40 were collected. Each thinking type was tested with a total of twenty questions: ten for preference and ten for ability. Higher ratings on a Likert scale indicated a greater affinity for the style in issue, with responses supplied. Descriptive statistics and t tests were used to see whether there were any variations in thinking styles. Results: The response rate was 88.4 percent (1172/1326). Males (69.5%) comprised the majority of paramedics with a median age of 36 (IQR 29–42) and the majority of them were primary or advanced care paramedics (PCP = 55.5%). Paramedic students (n = 268) had a median age of 23 years (IQR 21–26), most were male (63.1 percent), and most had finished high school (31.7 percent) or an under-graduate degree (25.4 percent) previous to paramedic education. Both groups rated their ability to utilise and preference for logical thinking much higher than their preference for experiential thinking. There was a statistically significant difference between paramedics and paramedic students in the mean score for logical thinking (p = 0.001). There was a statistically significant difference between paramedics and paramedic students in the mean score for experiential thinking. Working paramedics and student paramedics like and believe that they have the ability to think rationally rather than experientially. Our existing understanding of paramedic decision-making is enriched by this research, which has promise for enhancing paramedic training and clinical support systems.